Application of elementary school character education during the pandemic - Intan Fida Widyaningrum; Nur Alma Firoh; Syakirotul Lian Umillah (Prosiding University Research Colloquium, 2021)
Character education is an effort to build character, supporting the social,emotional and ethical development of students assisted by parents,teachers, and communities that are essential in the development anddevelopment of character learners. Character education is still a topic ofinterest to this day. Education that must make the young generationintelligent and moral, is still, in fact, going to have to keep on striving tomake it happen. In times of the current pandemic, the potential for childrenmust be consistently polished and well socialized in order for every child'scharacter to form and fully develop. Learning is nowadays done online,requiring children to use digital media. Digital media not only has a positiveimpact but also a negative impact that is a duty to educators, parents andcommunities in guiding and monitoring the child's digital media as bestthey can and thus benefiting themselves and their lives.